Numerical study on effective conditions for the induction of apoptotic temperatures for various tumor aspect ratios using a single continuous- wave laser in photothermal therapy using gold nanorods - Kim, Moojoong; Kim, Gwantaek; Kim, Donghyuk; Yoo, Jaisuk; Kim, Dong Kwon; Kim, Hyunjung (Cancers, 2019)
Photothermal therapy can serve as an alternative to classic surgery in the treatment of patients with cancer. However, using photothermal therapy can result in local overheating and damage to normal tissues. Therefore, it is important to determine effective heating conditions based on heat transfer. In this study, we analyzed laser–tissue interactions in gold nanoparticle (GNP)- enhanced photothermal therapy based on the theory of heat transfer. The thermal behavior inside tissues during photothermal therapy was analyzed using numerical analysis. The apoptosis ratio was defined by deriving the area having a temperature distribution between 43 °C and 50 °C, which is required for inducing apoptosis. Thermal damage, caused by local heating, was defined using the thermal hazard value. Using this approach, we confirmed that apoptosis can be predicted with respect to tumor size (aspect ratio) and heating conditions (laser intensity and radius) in photothermal therapy with a continuous-wave laser. Finally, we determined the effective apoptosis ratio and thermal hazard value of normal tissue according to tumor size and heating conditions, thereby establishing conditions for inducing maximal levels of cell apoptosis with minimal damage to normal tissue. The optimization conditions proposed in this study can be a gentle and effective treatment option for photothermal therapy.
Keywords: Apoptosis; Aspect ratio; Cancer; Gold nanoparticles; Heat transfer; Hyperthermia; Localized surface plasmonic resonance; NIR laser; Photothermal therapy; Thermal damage